PERHITUNGAN BIAYA PRODUKSI DENGAN METODE HARGA POKOK PROSES BASO ACI PADA UMKM BASO ACILA - Fadel Ilham Ramadhan; Lena Adela Prasmadhani; Maulida Isna Artanti; Halleina Rejeki Putri Hartono (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze production cost calculations at the Baso Acila UMKM using the process costing method. Data includes raw material costs, auxiliary materials, direct labor, and factory overhead for October 2024. The results reveal a total production cost of IDR 35,261,194, with a unit cost of IDR 7,836. Overhead accounts for the largest component (59.83%), while raw material costs represent the smallest component (4.07%). Compared to the SME's method, the process costing method offers more detailed cost allocation, especially for auxiliary materials and overhead. These findings highlight the importance of applying a more systematic cost accounting method to enhance efficiency and cost control.